AN ANALYSIS OF STUDENTS’ DIFFICULTIES IN SPEAKING SKILLS IN THE SECOND SEMESTER OF THE ENGLISH EDUCATION STUDY PROGRAM AT THE PGRI SILAMPARI UNIVERSITY - Triyogo, Agus; Andira, Rika; Hamdan, Hamdan (LP3MKIL, 2023)
This study aims to find out what difficulties hinder students from speaking English in the English study program, at PGRI Silampari University. This research uses qualitative research with a descriptive qualitative research design. The 23 students who participated in this study were selected based on a sample of second-semester students in the English language education study program at PGRI Silampari University. The questionnaire consists of 15 questions consisting of questions and statements used to collect data. Data analysis shows that there are a number of problems speaking English in the English language education study program caused by several inhibiting factors such as internal factors, external factors, the school system, environment and learning community. Speaking English in the English language education study program cannot be carried out without solving the problems of the inhibiting factors. So it can be concluded that speaking English will be effective and efficient if students and lecturers always speak English with each other and can make some discipline or give sanctions such as giving bad grades, and so on. To be obeyed to speak English in the English language education study program, PGRI Silampari University.